2000
DOI: 10.1007/s002030000148
|View full text |Cite
|
Sign up to set email alerts
|

Initial steps in the fermentation of 3-hydroxybenzoate by Sporotomaculum hydroxybenzoicum

Abstract: The anaerobic bacterium Sporotomaculum hydroxybenzoicum ferments 3-hydroxybenzoate to acetate, butyrate, and CO 2 . 3-Hydroxybenzoate was activated to 3-hydroxybenzoyl-CoA in a CoA-transferase reaction with acetyl-CoA or butyryl-CoA as CoA donors. 3-Hydroxybenzoyl-CoA was reductively dehydroxylated, forming benzoyl-CoA. This reaction was measured in cell-free extracts with cob(I)alamin as low-potential electron donor. No evidence was obtained that cob(I)alamin is the physiological electron donor; however, inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…In vitro assays with glutarate-, benzoate-, and 3-hydroxybenzoate-fermenting bacteria suggested that glutaconylCoA is the product released from glutaryl-CoA dehydrogenase without a concomitant decarboxylation to crotonyl-CoA. The subsequent decarboxylation is then catalyzed by a membrane-bound, sodium ion-pumping glutaconyl-CoA decarboxylase containing a biotin cofactor (15,28,30). In accordance, the genes coding for such a decarboxylase are present in the genome of the benzoate-fermenting organism Syntrophus aciditrophicus (29).…”
mentioning
confidence: 76%
“…In vitro assays with glutarate-, benzoate-, and 3-hydroxybenzoate-fermenting bacteria suggested that glutaconylCoA is the product released from glutaryl-CoA dehydrogenase without a concomitant decarboxylation to crotonyl-CoA. The subsequent decarboxylation is then catalyzed by a membrane-bound, sodium ion-pumping glutaconyl-CoA decarboxylase containing a biotin cofactor (15,28,30). In accordance, the genes coding for such a decarboxylase are present in the genome of the benzoate-fermenting organism Syntrophus aciditrophicus (29).…”
mentioning
confidence: 76%
“…been reported, e.g., in the 3-hydroxybenzoate degradation pathway from the fermenting bacterium Sporotomaculum hydroxybenzoicum (259) or in the peripheral toluene degradation pathway (218) (see below).…”
Section: Benzoate Catabolism: the Benzoyl-coa Degradation Pathwaymentioning
confidence: 99%
“…As the first step in the degradation pathway, 3-hydroxybenzoate was activated to 3-hydroxybenzoyl-CoA in a CoA transferase-mediated reaction with acetyl-CoA or butyryl-CoA as the CoA donor. The use of a CoA transferase rather than a CoA ligase (ATP-consuming) reaction for substrate activation has important energetic implications for this fermenting bacterium and constitutes an important exception to the general principle of the activation of aromatic acid compounds by CoA ligases (259). A third pathway for anaerobic 3-hydroxybenzoate degradation that involves hydroxylation reactions to form HHQ has been reported for the denitrifying bacterium strain BoNHB (320).…”
Section: -Hydroxybenzoate Catabolismmentioning
confidence: 99%
“…This would allow further metabolism to acetyl-CoA through the benzoyl-CoA pathway (8). The reductive elimination of the m-hydroxyl group has only been demonstrated so far in a fermenting bacterium, Sporotomaculum hydroxybenzoicum (11,27) (Fig. 7B).…”
Section: Discussionmentioning
confidence: 94%
“…It remains to be shown which isomeric form of the dienoyl-CoA is formed. The genes coding for benzoyl-CoA reductase, for the electron donor ferredoxin, and (11,27). (C) Denitrifying strain BoNHB (33).…”
Section: Discussionmentioning
confidence: 99%